Anxiety control and metacognitive beliefs mediate the relationship between inflated responsibility and obsessive compulsive symptoms. Issue 3 (30th August 2015) - Sassaroli, Sandra; Centorame, Francesco; Caselli, Gabriele; Favaretto, Ettore; Fiore, Francesca; Gallucci, Marcello; Sarracino, Diego; Ruggiero, Giovanni M.; Spada, Marcantonio M.; Rapee, Ronald M.
Abstract: Research has indicated that beliefs about inflated responsibility, beliefs about perceived control over anxiety-related events and reactions (anxiety control) and metacognitive beliefs about the need to control thoughts are associated with obsessive compulsive symptoms. In the current study we tested a mediation model of the interactions between these variables in predicting obsessive compulsive symptoms. Thirty-seven individuals with obsessive compulsive disorder and 31 controls completed the following self-report instruments: the Responsibility Attitude Scale, the Anxiety Control Scale, the Beliefs about Need to Control Thoughts sub-scale of the Metacognitions Questionnaire 30, and the Padua Inventory. Mann-Whitney U tests revealed that participants in the clinical group scored significantly higher than those in the non-clinical group on all variables. In the mediation model we found that the relationship between beliefs about inflated responsibility and obsessive compulsive symptoms was fully mediated by anxiety control and beliefs about the need to control thoughts. These findings provide support for the significant role played by beliefs about control in predicting the severity of obsessive compulsive symptoms. Highlights: Interaction between cognitive and metacognitive predictors of OCD. Responsibility, perceived control over anxiety and beliefs about the need to control. Patients with obsessive compulsive disorder and normal controls participated. Anxiety control and the need to control thoughts mediated between responsibility and OCD. Anxiety control and the thoughts control play a role in cognitive models of OCD.